Corrosion behavior of TiO2‐coated Ti–6Al–7Nb surfaces obtained by anodic oxidation in sulfuric or acetic acid. Issue 7 (27th November 2014) - Cotolan, N.; Pop, A.; Marconi, D.; Ponta, O.; Muresan, L. M.
<x xml:space="preserve">Abstract</x> The morpho‐structural and electrochemical properties of the oxide film formed on the implants surface play a decisive role for the bio‐compatibility of titanium‐based prosthesis. The aim of the present work is to investigate and compare the corrosion behavior of titanium dioxide (TiO2) coated Ti–6Al–7Nb prepared by anodic oxidation in two different electrolytes (1 M acetic acid (CH3COOH) and sulfuric acid (H2SO4) solutions) and at two different oxidation potentials. The corrosion behavior of oxidized samples was investigated in Hank's simulated physiological solution, using cyclic polarization method and electrochemical impedance spectroscopy and the obtained results were compared with those recorded on bare Ti–6Al–7Nb in the same experimental conditions. The oxidation in CH3COOH was proven to be more beneficial for the corrosion resistance of Ti–6Al–7Nb samples than the oxidation in H2SO4 of same concentration.